2022
DOI: 10.1038/s41467-022-32482-y
|View full text |Cite
|
Sign up to set email alerts
|

Moisture-triggered fast crystallization enables efficient and stable perovskite solar cells

Abstract: Understanding the function of moisture on perovskite is challenging since the random environmental moisture strongly disturbs the perovskite structure. Here, we develop various N2-protected characterization techniques to comprehensively study the effect of moisture on the efficient cesium, methylammonium, and formamidinium triple-cation perovskite (Cs0.05FA0.75MA0.20)Pb(I0.96Br0.04)3. In contrast to the secondary measurements, the established air-exposure-free techniques allow us directly monitor the influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(81 citation statements)
references
References 57 publications
1
80
0
Order By: Relevance
“…As shown in Figure g,i and Figure S7, SEM results show that the use of SnO 2 or our specially selected PTAA as the substrate has little effect on the perovskite morphology, and both of them can reflect the effect of FAFa treatment on the perovskite. At the same time, other studies have also shown that the method of using PTAA to study the properties of the perovskite buried interface is reliable. , …”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…As shown in Figure g,i and Figure S7, SEM results show that the use of SnO 2 or our specially selected PTAA as the substrate has little effect on the perovskite morphology, and both of them can reflect the effect of FAFa treatment on the perovskite. At the same time, other studies have also shown that the method of using PTAA to study the properties of the perovskite buried interface is reliable. , …”
Section: Resultsmentioning
confidence: 92%
“…At the same time, other studies have also shown that the method of using PTAA to study the properties of the perovskite buried interface is reliable. 41,53 XPS was performed to analyze the bonding state of O, Pb, and I in the top and bottom sides of the perovskite films in Figure 3c,d and Figure S8. Compared with the pristine perovskite−ETL interface (hereafter denoted as FAFa-0bottom), the binding energy of O 1s of the perovskite-ETL interface treated with 2 mg/mL FAFa (FAFa-2-bottom) is decreased by 0.15 eV, and the binding energy of Pb 4f is increased by 0.15 eV, as shown in Figure 3c,d.…”
Section: Buried Interface Lift-off and Characterizationmentioning
confidence: 99%
“…The impact of H2O on perovskite solar cells has been widely studied. [36][37][38][39][40][41][42] Moderate water additives/moisture could accelerate the crystal formation and enhance the texture-orientation of the perovskite films, which could lead to higher efficiency of perovskite solar cells. 37,38,40,42 However, few studies have demonstrate moisture treatment for perovskite light-emitting diodes.…”
Section: Water Additives and Two-step Annealing In Fabrication Processmentioning
confidence: 99%
“…[36][37][38][39][40][41][42] Moderate water additives/moisture could accelerate the crystal formation and enhance the texture-orientation of the perovskite films, which could lead to higher efficiency of perovskite solar cells. 37,38,40,42 However, few studies have demonstrate moisture treatment for perovskite light-emitting diodes. 43 The intentional addition of water to the perovskite precursor solutions was inspired by previous work with CH3NH3PbBr3 thin films, where a water additive was used to tune the crystallization in the spin coating process.…”
Section: Water Additives and Two-step Annealing In Fabrication Processmentioning
confidence: 99%
“…According to past reports, it has been demonstrated that traces of water could also play a positive role in the formation of perovskite films. 90 The optimal humidity could favour the formation of perovskite and promote the crystallization with the improved PL. 91,92 In such bi-phase and multiphase systems, a stable interface may form between different phases, promoting the ion exchange channels.…”
Section: Interface Engineering Of Mhp Ncsmentioning
confidence: 99%